Evaluación de la reducción de pelets utilizando carbón como agente reductor - Pérez Velásquez, Sandra Patricia; López Díaz, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Obtaining the steel is done from iron ore or scrap metal. In the first case, the process takes place via a blast furnace-converter, in the second, via an electric arc furnace. However, the so-called pre-reduced iron ore pellets can also be charged to the electric furnace, metallic materials that can be obtained from iron ore fines (carrier of the metallic charge), coal fines (reducing agent), fines lime (desulfurizing agent) and bentonite (binder), which are converted into ovoids using a pelletizing disc. The work shows the characterization carried out on the raw materials, the reducibility tests carried out on pellets loaded in a Linder-type furnace - manufactured from two Colombian iron ore deposits - and the design and construction of a furnace to evaluate the behavior of the pellets during reduction.